Determinan Stres Kerja Pada Penjaga Palang Pintu Rel Kereta Api Resmi Resort 9.6 Daerah Operasi IX Di Kabupaten Jember - Dhanny Indra Prasetya; Isa Ma’rufi; Reny Indrayani (Politeknik Negeri Jember, 2018)
Abstract Transportation sector development is one of the sub sectors that is important to support economic development. Poor transportation sector will develop human activities. One type of transportation is a train that has a special line and avoid congestion, Sometimes the train also cut off the highway, so the railway door is made to function to secure the train journey and guarded the door keepers. The problem in the concern at PT KAI is human error, One example of human error is a door keepers undisciplined in closing the railway door gates. One of the danger areas is Jember Regency which is located in DAOP IX, it is because Jember Regency had the most railway door in DAOP IX and has many crossings in the settlement area. The results of observations before the study found some workers who show symptoms of work stress. Jember regency had 12 official railway door and there are 47 door keepers who are all male. The door keepers are mostly 25-40 years old, have a working period of 1-5 years, have married marriage status, and have children <3, have wage / salary Rp.1.500.000-Rp.3.500.000, almost half of the respondents experienced fatigue and severe stress. The results of the study found there is a relationship between age, employment, marital status, wages / salary with work stress, but fatigue and wages/salary are not related to work stress.Keywords: Work Stress, Human error, Door keepers.